الاقتباس والتناص من القرآن الكريم لدى شعراء مجلة الأدب الإسلامي = al-Iqtibas wa-al-tanas min al-Qur'an al-katim lada shu'ara'majallat al-adab al-Islami - Bahjat, Munjid Mustafa; al-Nu'aymi, Anas Husam (Scientific Publishing Center, 2013)
Adapting texts from the Qur'an is considered one of the necessary requirements of eloquence and fluency for every speaker of the Arabic language and every literary man regardless of whether he composes poetry or writes prose. Adaptation is a phenomenon that is studies and analyzed by the scholars of eloquence and literary criticism. As for intertextuality, it is one of the poetic styles and artistic techniques which is commonly used by modern and contemporary poets. Moreover, poets celebrated its use, as a way of creating interrelations between texts, which in turn enriches the text as a whole. This enrichment contributes to the enhancement of the aesthetic structure of the text in the first place. Just like adaptation , intertextuality is also a phenimenon closely studied by contemporary critics, who attempted to define it, identify its types, its different forms, itseffect on the text and its analysis and its effect on the listener. This research paper will attempt to define the two phenomena of adaptation and intertextuality. In addition, the paper will discuss the level of adaptation and intertextuality among the poets of the league of Islamic literature by analysing their poetic texts texts published in the magazine of the league starting from its issue to the fortieth in a period spanning 10 years from 1993 to 20014. The research paper will rely on the inductive analytical methodology and will consist of three parts. The first part deals with the definition of the two terms. The second part will discuss adaptation, its types, levels and some of its examples. The third part will discuss intertextuality, its types, levels and some of its examples.